The birth of Japanese historiography - Bentley, John R., author.
1 online resource.
Keywords: "As the first book in English on the origins of Japanese historiography, using both archaeological and textual data, this book examines the connection between ancient Japan and the Korean kingdom of Paekche and how tutors from the kingdom of Kara helped to lay the foundation for a literate culture in Japan. Illustrating how tutors from the kingdoms of Kara and Paekche taught Chinese writing to the Japanese court through the prism of the highly civilized culture of Paekche, the book goes on to argue that Paekche tutors guided the early Japanese court through writing, recording family history, and ultimately an early history of the ruling family. As the Japanese began to create their own history, they relied on Paekche histories as a model. Triangulating textual data from Kojiki, Nihon shoki, and Sendai kuji hongi, the author here demonstrates that various aspects of early king genealogies and later events were manipulated. Offering new theories about the Japanese ruling family, it is posited that Emperor Jitō had her committee put Jingū in power, and Suiko on the throne in place of original male rulers to create images of strong, female rulers, as she envisioned herself. The Birth of Japanese Historiography will be a valuable resource for students and scholars of Japanese history, historiography and linguistics"--